PENGARUH PENYULUHAN KESEHATAN TERHADAP PENGETAHUAN IBU HAMILTENTANG PENCEGAHAN PENULARAN COVID-19 SELAMA MASA KEHAMILAN DI WILAYAH KERJA PUSKESMAS PANGKALAN KERINCI - Farizal, Ekry Binti; Romlah, Siti (Ensiklopedia of Journal, 2021)
Corona Virus Disease 2019 (Covid-19) is an acute respiratory disorder caused by the SARS-CoV-2 virus and has become a worldwide pandemic. Covid-19 has infected the entire world population, not pregnant women. The susceptibility of pregnant women to infection is the background for the need for studies on the effects of Covid-19 on the mother, fetus, and newborn baby. The purpose of the study was to determine the effect of health education on the knowledge of pregnant women about preventing transmission of COVID-19 during pregnancy at the pangkalan kerinci Health Center. The type of research is quantitative and quasi-experimental design. The population is pregnant women and the sample is 126 people, with purposive sampling. The research instruments were questionnaires and leaflets. Data analysis used univariate and bivariate. The univariate results given by respondents before counseling with Leaflets had a lack of knowledge as much as 62.7% and before counseling with Leaflets they had good knowledge as much as 69.8%. The results of the Wilcoxon statistical test showed a p value of 0.000, which means that the p value < which indicates the use of leaflet media is effective on mothers' knowledge about preventing Covid 19 at the pangkalan kerinci Health Center. It is hoped that the Puskesmas will understand cadres in providing information about preventing Covid 19 during pregnancy.Keywords        : Knowledge, Leaflet, and Covid 19